Peran Pendidikan Agama Kristen dalam Pengembangan Spiritualitas Dewasa - Tiurma Berasa; Dita Natania Sinaga; Mawarni Hutagalung; Revi Sihombing (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education has an important role in forming individuals intellectually and spiritually, especially through Christian Religious Education (PAK). Spiritual maturity reflects a person's ability to live according to Christian values ​​such as love, forgiveness, and humility. This process involves learning, social experiences, and a deep appreciation of the faith. PAK not only teaches theological knowledge, but also instills moral values ​​that guide daily life. In the midst of the challenges of the modern era, PAK helps individuals develop spiritual awareness, integrate Christian values ​​in social relationships, and face life's challenges wisely. Through a holistic approach, PAK forms a character that is oriented towards intellectual achievement and real life transformation. This education creates individuals who are balanced between intellectual and spiritual intelligence, contributing to building a society full of love, harmony and meaning.